1984
DOI: 10.1002/ijc.2910330310
|View full text |Cite
|
Sign up to set email alerts
|

Initial clinical evaluation of an immunoradiometric assay for CA 19‐9 using the nci serum bank

Abstract: More than 1,600 coded sera obtained from blood donors and the NCI/Mayo Clinic Serum Bank were analyzed with an improved immunoradiometric assay for the carbohydrate antigenic determinant, CA 19-9. Results indicated that CA 19-9 is elevated in a large fraction of sera (67%) from patients with advanced adenocarcinomas of the upper gastrointestinal (GI) tract, including those with pancreatic, hepatobiliary and gastric carcinomas. Several of these sera had CA 19-9 exceeding 300,000 U/ml. A smaller fraction (18%) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
52
1
3

Year Published

1986
1986
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(60 citation statements)
references
References 7 publications
4
52
1
3
Order By: Relevance
“…Therefore, patients with oesophagitis, the most common benign condition of the oesophagus which can also present with dysphagia, were investigated for the presence of CA19-9 in the serum. Ritts et al (1984), in a series of eight patients with oesophageal cancer, noted one patient (13%) to have a CA19-9 level of >40Uml-1. Our series has shown that elevated levels of CA19-9 are present in 34% of patients with oesophageal cancer at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Therefore, patients with oesophagitis, the most common benign condition of the oesophagus which can also present with dysphagia, were investigated for the presence of CA19-9 in the serum. Ritts et al (1984), in a series of eight patients with oesophageal cancer, noted one patient (13%) to have a CA19-9 level of >40Uml-1. Our series has shown that elevated levels of CA19-9 are present in 34% of patients with oesophageal cancer at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 97%
“…Although the CA19-9 assay was originally developed to detect patients with colorectal adenocarcinoma (Koprowski et al, 1981), subsequent work revealed that the serum levels of this antigen were raised in a greater proportion of patients with pancreatic and hepatobiliary malignancies than those with large bowel cancer (Ritts et al, 1984;Kew et al, 1987). The oesophagus, like the pancreas and the liver, is a foregut derivative and this study was undertaken in the hope that CA19-9 might prove a useful tumour marker for oesophageal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated serum CA 19-9 levels have previously been found in many different malignant diseases (Herlyn et al, 1982;Del Villano et al, 1983;Jalanko et al, 1984;Kuusela et al, 1984;Ritts et al, 1984). The test seems especially promising for the detection of pancreatic cancer, 70-79% of these patients showing increased serum CA 19-9 concentrations (Del Villano et al, 1983;Ritts et al, 1984).…”
mentioning
confidence: 96%
“…-Određivanje CEA se ne preporučuje za skrining kolorektalnog karcinoma; -CEA se može određivati pre hiruškog zahvata kod pacijenata sa kolorektalnim karcinomom kao pomoć pri utvrđivanju patološkog stadijuma bolesti i planiranju tretmana; -CEA ne treba koristiti u neposrednom postoperativnom periodu; -CEA se može meriti postoperativno ako je resekcija metastaza na jetri klinički indukovana; -CEA se može meriti za vreme tretmana radi praćenja odgovora na terapiju i dokumentovanja faze bolesti [13,36] Gastrointestinalni karcinom antigen (CA 19-9) je glikolipid, derivat krvne grupe Levis a/b [33]. Identifikovan je kao tumorski marker 1981. godine.…”
Section: Klasifikacija Tumorskih Markera Na Biohemijskoj Osnoviunclassified